Tailoring consumer resources to enhance self-care in chronic heart failure - Driscoll, A.; Davidson, Patricia; Clark, R.; Huang, N.; Aho, Z. (Elsevier Inc, 2009)
Summary. Background: Chronic heart failure (CHF) is associated with high hospitalisation and mortality rates and debilitating symptoms. In an effort to reduce hospitalisations and improve symptoms individuals must be supported in managing their condition. Patients who can effectively self-manage their symptoms through lifestyle modification and adherence to complex medication regimens will experience less hospitalisations and other adverse events. Aim: The purpose of this paper is to explain how providing evidence-based information, using patient education resources, can support self-care. Discussion: Self-care relates to the activities that individuals engage in relation to health seeking behaviours. Supporting self-care practices through tailored and relevant information can provide patients with resources and advice on strategies to manage their condition. Evidence-based approaches to improve adherence to self-care practices in patients with heart failure are not often reported. Low health literacy can result in poor understanding of the information about CHF and is related to adverse health outcomes. Also a lack of knowledge can lead to non-adherence with self-care practices such as following fluid restriction, low sodium diet and daily weighing routines. However these issues need to be addressed to improve self-management skills.Outcome: Recently the Heart Foundation CHF consumer resource was updated based on evidence-based national clinical guidelines. The aim of this resource is to help consumers improve understanding of the disease, reduce uncertainty and anxiety about what to do when symptoms appear, encourage discussions with local doctors, and build confidence in self-care management.Conclusion: Evidence-based CHF patient education resources promote self-care practices and early detection of symptom change that may reduce hospitalisations and improve the quality of life for people with CHF.